2004
DOI: 10.1182/blood-2003-02-0546
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase inhibition with an oligonucleotide telomerase template antagonist: in vitro and in vivo studies in multiple myeloma and lymphoma

Abstract: The effects of telomerase inhibition with an oligonucleotide N3 3 P5 thiophosphoramidate (GRN163) complementary to the telomerase template region were examined on human multiple myeloma (MM) and non-Hodgkin lymphoma (NHL) cell lines, primary MM cells, and tumor xenografts. GRN163 treatment reduced telomerase levels in all cells and induced more rapid telomeric shortening. Continuous GRN163 treatment for 7 to 14 days resulted in proliferative arrest, morphologic changes, and apoptosis characteristic of cell cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 38 publications
(68 reference statements)
3
43
0
Order By: Relevance
“…11 Studies in various adult and pediatric cancer cell lines have demonstrated that imetelstat, but not a mismatch oligonucleotide control, inhibited cell proliferation, colony formation, and invasiveness. [11][12][13][14][15][16][17][18] Phase 1 and 2 clinical trials demonstrated a favorable pharmacokinetic and side effect profile for imetelstat, though with mixed clinical results. 14,[19][20][21][22][23] Although telomerase activity is regulated largely at the level of transcription of TERT, the gene that encodes the catalytic component of the telomerase enzyme complex, it has become clear that telomerase regulation is complex and also involves posttranslational modifications, alternative splicing, and binding to chaperone proteins.…”
Section: Introductionmentioning
confidence: 99%
“…11 Studies in various adult and pediatric cancer cell lines have demonstrated that imetelstat, but not a mismatch oligonucleotide control, inhibited cell proliferation, colony formation, and invasiveness. [11][12][13][14][15][16][17][18] Phase 1 and 2 clinical trials demonstrated a favorable pharmacokinetic and side effect profile for imetelstat, though with mixed clinical results. 14,[19][20][21][22][23] Although telomerase activity is regulated largely at the level of transcription of TERT, the gene that encodes the catalytic component of the telomerase enzyme complex, it has become clear that telomerase regulation is complex and also involves posttranslational modifications, alternative splicing, and binding to chaperone proteins.…”
Section: Introductionmentioning
confidence: 99%
“…18 Preclinical studies revealed that a development candidate from this class of oligonucleotides, GRN163, inhibited telomerase activity in various cultured human cancer cell lines (breast, renal, prostate, epidermoid, cervix, lung, colon, leukemia, multiple myeloma, lymphoma) leading to telomere shortening, growth arrest, and apoptosis. [23][24][25][26][27] In addition, GRN163 inhibited tumor growth of prostate cancer, multiple myeloma, lymphoma, and glioblastoma in xenotransplant models. 24,26,27 To evaluate the potential use of NPSS oligonucleotides targeting the human telomerase RNA component for the treatment of HCC, we analyzed GRN163 and GRN163L, a lipid-conjugated derivative of GRN163 designed for increased bioavailability, 28 for antitumor effects against human hepatoma cells (Hep3B and Huh7) in vivo and in vitro.…”
mentioning
confidence: 99%
“…[23][24][25][26][27] In addition, GRN163 inhibited tumor growth of prostate cancer, multiple myeloma, lymphoma, and glioblastoma in xenotransplant models. 24,26,27 To evaluate the potential use of NPSS oligonucleotides targeting the human telomerase RNA component for the treatment of HCC, we analyzed GRN163 and GRN163L, a lipid-conjugated derivative of GRN163 designed for increased bioavailability, 28 for antitumor effects against human hepatoma cells (Hep3B and Huh7) in vivo and in vitro. The results suggest that telomerase inhibition could be a valid approach for HCC treatment and that GRN163L is a promising drug development candidate with significant effects on tumor growth and increased chemosensitivity to doxorubicin.…”
mentioning
confidence: 99%
“…GRN-163 has demonstrated potent inhibitory activity against human telomerase in several biochemical assays, with IC 50 values of < 1 nM (Gryaznov et al, 2001;Herbert et al, 2002). In vitro, telomerase inhibition by GRN-163 induced cellular senescence and apoptosis in various human cancer cell lines (Ozawa et al, 2004;Asai et al, 2003;Herbert, 2002;Akiyama et al, 2003;Wang et al, 2004). Although a potential limitation of oligonucleotide therapies is the bioavailability in tumor tissues (Corey, 2002), GRN-163 inhibited tumor growth in prostate cancer, multiple myeloma, lymphoma, hepatoma and glioblastoma xenografts in rodents (Ozawa et al, 2004;Asai et al, 2003;Wang et al, 2004;Hashizume et al, 2008;Djojosubroto et al, 2005).…”
Section: Intranasal Delivery Of a Telomerase Inhibitormentioning
confidence: 99%
“…In vitro, telomerase inhibition by GRN-163 induced cellular senescence and apoptosis in various human cancer cell lines (Ozawa et al, 2004;Asai et al, 2003;Herbert, 2002;Akiyama et al, 2003;Wang et al, 2004). Although a potential limitation of oligonucleotide therapies is the bioavailability in tumor tissues (Corey, 2002), GRN-163 inhibited tumor growth in prostate cancer, multiple myeloma, lymphoma, hepatoma and glioblastoma xenografts in rodents (Ozawa et al, 2004;Asai et al, 2003;Wang et al, 2004;Hashizume et al, 2008;Djojosubroto et al, 2005). GRN-163 has been delivered successfully into the brain using IND and shown impressive oncolytic activity without harming normal brain tissue (Hashizume et al, 2008).…”
Section: Intranasal Delivery Of a Telomerase Inhibitormentioning
confidence: 99%